ANALISIS STRATEGI PERUBAHAN BISNIS PT BATA INDONESIA - Pamungkur Pamungkur; Sunarmie Sunarmie (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
PT. Bata Indonesia is a company engaged in footwear manufacturing and retail industry. The increasing competition in today’s business world becomes a challenge for the company to keep competing and surviving in the competition. The research method used in this research is descriptive method with case-study research type. The research data collection technique is survey which was carried through interviews and questionnaires with the company director and general service manager of the sales department. The collection of data obtained was analyzed using SWOT analysis. For in order to make an accurate strategy for a company to run, it is necessary to begin with reviewing the company’s strengths, weaknesses, opportunities, and also threats for the company. From the SWOT analysis undertaken, it was figured that the IFAS value is 2,64584 and the EFAS value is 2,32827. Moreover, the IE matrix showed that the company’s position is in the concentration strategy through horizontal integration or stability. This is a state where the company is experiencing a period of growth. These results inferred that the fittest strategy the company should implement is a growth strategy through horizontal integration. It is an activity to expand the company by building outlets, stores, and mall sales in as many cities as possible in Indonesia, and also to improve the products through product innovations. The result of SWOT diagram also showed that the company carries out aggressive strategy or at quadrant 1 that possesses positive value. From the research results, it can be concluded that the company should implement SO (Strengths-Opportunities) strategy for the company to maintain the ability to survive in the business competition.